Estudo da ligação de vigotas pré-moldadas protendidas com concreto moldado no local em lajes nervuradas - Moreira, Renato Barbosa (2016)
The aim of this paper is to present an experimental research conducted in the laboratory, designed to analyze the adhesion between the prestressed beams produced in precast factory, and the concrete cover molded on site, forming panels of ribbed slabs. 18 prototypes were tested with a width of 100 cm, compounds with two beams, length 215 cm and 13 cm and 9 cm and 4 cm from the joist concrete cover molded on site. The input variables were the texture of the upper surface of the joists, the slump, maximum dimension characteristic of aggregate concrete and the influence of conduits on the table. The results were calculated longitudinal shear stresses acting on the composite section and compared with the last values recommended by PCI (2004), NBR 9062 (2006), FIB MC (2010) and the Spanish standard EF (1996). The analysis of the influence of variables was performed by correlation and ANOVA. They were also measured specific concrete deformations in 4 regions of the cross section and compared the strain values in concrete cast in place and precast concrete. After the rupture was checked by visual examination on all prototypes to verify the state of the interface after the test. The results showed that the values of the shear stresses acting on the break overcame the values recommended by the rules and that there was no slip at the interface between precast concrete and cast-in-place. In ANOVA it was observed that the surface roughness, the presence of conduits and the slump not affect the behavior of the section and so little influenced at rupture and shear stresses acting. The study also showed that the fck of the concrete topping also not proved to be relevant, although the prototypes smaller fck values for the concrete topping showed detachment or cover displacement trend for the rupture loads. The shear stresses acting on the flexure showed values higher than those recommended by international standards and organizations. The results of the displacements and deformations indicated a concrete supportive behavior between the concrete beams and the table and maintained trend behavior for all kinds of prototypes, differing only in shear stress. The presence of the beam at the end of the prototypes prevented the sliding at the interface between the precast concrete and cast in place.